(untitled) (Journal of Hama University, 2024)
The research aims to identify the degree of use of smart phone applications by students of the College of Education in all its departments (curriculam and teaching methods, psychological counseling, and child rearing), and to identify the differences between the estimates of respondents about the use of smart phone applications, due to the variable of specialization, In order to achieve the objectives of the research, the descriptive approach was used by designing a questionnaire consisting of (23) items, which was distributed to (100) students from the Faculty of Education at Tishreen University. The research reached the following results: The degree of use of smart phone applications by students of the College of Education in all its departments (curriculam and teaching methods, psychological counseling, and child rearing) for learning was high, The researcher suggested the need to conduct more studies to detect smart phone applications in the educational process in different educational stages.